Multiple risk factors for persistent HBV viraemia in an adult receiving nucleos/tide analogue therapy - Lumley, Sheila F (Sex Transm Infect, 2024)
Diagnosing and treating chronic hepatitis B virus (HBV) infection are key interventions to support progress towards elimination of viral hepatitis by 2030. Although nucleos/tide analogue (NA) therapy is typically highly effective, challenges remain for viral load (VL) suppression, including medication access, incomplete adherence, and drug resistance. We present a case of a long-term HBV and HIV co-infected adult prescribed sequential NA therapy regimens, with episodes of breakthrough viraemia. Multiple factors contribute to virologic breakthrough, including exposure to old NA agents, initial high HBV VL, therapy interruptions, intercurrent illnesses and potential contribution from resistance mutations. The case underscores the importance of individualized treatment approaches and adherence support in achieving HBV suppression. Furthermore, it emphasizes the need for improved clinical pathways addressing education, support, and access to care, particularly for marginalized populations. Comprehensive data collection inclusive of underrepresented individuals is crucial for maintaining retention in the care cascade, and informing effective interventions.